Mechanical spectroscopy of deformed WE43 magnesium alloys - Lambri, Osvaldo Agustin F. (2006)
Ageing commercial WE43 magnesium alloys at 643K for various times up to 10,000 s promotes the development of P1 precipitates, which strengthen the matrix. However, overageing causes P2 precipitates, which soften the matrix, to develop. Room temperature plastic deformation of samples aged at 643K causes (a) the generation of new dislocations and (b) the dissolution of the previously developed strengthening P1 precipitates. These effects are revealed by (a) the decreased micro yield stress, (b) the increased part of the measured internal friction which is independent of the amplitude, and (c) the decreased integrated intensity of the diffraction peak related to P1.